Sociolinguistic variation in children's language acquiring community norms - Smith, Jennifer 1970-; Durham, Mercedes (Cambridge University Press, 2019)
How we vary our speech is fundamental in signalling who we are, where we're from and where we're going. How and when does such variation arise? Here, leading experts Jennifer Smith and Mercedes Durham address this question through a sociolinguistic analysis of the speech of preschool children in interaction with their primary caregivers. Bringing together two fields of linguistic research - variationist sociolinguistics and first language acquisition - the study focusses both qualitative and quantitative analysis of a range of variables to show when and how variation is acquired by young children, and the effect the caregiver's interaction has on this process. In doing so, they tackle a fundamental question in language research: when and how do children acquire the highly complex patterns of variation widely attested in adult speech?
Title from publisher's bibliographic system (viewed on 09 May 2019)
Keywords: Soziolekt; Spracherwerb; Englisch; Kind; Language acquisition; Communicative competence in children; Language awareness in children